THE DIFFERENCE OF STROKE FACTOR BETWEEN PATIENT WHO LIVE IN RURAL AND URBAN AREA IN RSUP Dr. SARDJITO - , NIK MUHAMMAD TORIQ B NIKMANSOR; , dr. H. Abdul Gofir, Sp.S (K) ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Stroke is a worldwide disease problem which does not only worried the poor countries, but in well-developed countries that have high standard of medical care as well. Stroke can be categorised into haemorrhagic and ischaemic stroke. Some of the risk factors are hypertension, cardiac disease, diabetes, heredity, blood lipids, cholesterol, smoking, diet/obesity, soft water, race, age, gender, haematocrit, and oral contraceptives. These risk factors can be categorised into modifiable and unmodifiable. The data of the risk factors of the stroke patients will be traced and taken from the stroke patientâs medical records. The main objective of this study is to find out what are the dominant stroke risk factors among the stroke patients in each rural and urban area. With this data in each area, we can use it to do earlier prevention and decrease the incidence of stroke. Aim: To determine the differences of stroke risk factors among the stroke patients who live in rural and urban area in RSUP Dr. Sardjito. Methods: This is a non-experimental research